Association between malnutrition and long-term mortality in older adults with ischemic stroke. Issue 5 (May 2021) - Yuan, Kang; Zhu, Shuanggen; Wang, Huaiming; Chen, Jingjing; Zhang, Xiaohao; Xu, Pengfei; Xie, Yi; Zhu, Xinyi; Zhu, Wusheng; Sun, Wen; Xu, Gelin; Liu, Xinfeng
Summary: Background & aims: Malnutrition is associated with poor prognosis of different diseases. This study aimed to investigate the association of malnutrition with long-term mortality of older adults with ischemic stroke in China. Methods: We selected patients aged ≥65 years with first-ever ischemic stroke from the Nanjing Stroke Registry Program. Malnutrition was defined according to the controlling nutritional status score (CONUT), the geriatric nutritional risk index (GNRI), and the prognostic nutritional index score (PNI), respectively. Multivariable Cox proportional hazards regressions and competing risk regressions were performed to explore the relationship between malnutrition and the risk of mortality in older adults with ischemic stroke. Results: Among 1065 enrolled patients, 60.5%, 46.7%, and 30.6% of patients were malnourished according to CONUT, GNRI, and PNI score. During a median follow-up of 4.74 (3.73–5.82) years, 205 (19.2%) patients died. In multivariate analysis, malnutrition (severe risk versus normal nutrition) was associated with significantly increased risk for mortality by the CONUT (adjusted hazard ratio [HR] 4.615, 95% confidence interval [CI] 1.373–15.514, P  = 0.013), GNRI (adjusted HR 3.641, 95% CI 1.924–6.891, P  < 0.001), and PNI score (adjusted HR 1.587, 95% CI, 1.096–2.297, P  = 0.014). Furthermore, adding the malnutrition indexes to models modestly improved the predictive ability of mortality. Conclusions: Our study indicated that malnutrition was highly prevalent in older Chinese adults with ischemic stroke and associated with increased mortality. Further research is required to evaluate the efficacy of nutritional management in these patients.